2012
DOI: 10.3109/00016357.2012.697576
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of periodontal pathogens in amniotic fluid and the role of periodontal disease in pre-term birth and low birth weight

Abstract: These findings suggest that the transmission of some periodontal pathogens from the oral cavity of the mother may cause adverse pregnancy outcomes. The results contribute to an understanding of the association between periodontal disease and PTLBW, but further studies are required to better clarify the possible relationship.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
64
0
6

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(73 citation statements)
references
References 27 publications
0
64
0
6
Order By: Relevance
“…As a periodontal pathogen, P. gingivalis may indirectly contribute to adverse pregnancy outcomes (APO) by facilitating the release of bacterial products or inflammatory mediators into the maternal circulation that reach the maternal-fetal interface [2]. P. gingivalis could also directly promote APO via invasion and injury to utero-placental tissues; this is supported by several studies that have detected P. gingivalis DNA/antigen in the placenta, amniotic fluid, umbilical cord, and neonatal nasogastric aspirates from complicated pregnancies [3][4][5][6][7][8][9][10][11]. However, the significance of P. gingivalis as a causative agent of APO is sometimes viewed with skepticism due to several confounding factors.…”
Section: Introductionmentioning
confidence: 63%
See 2 more Smart Citations
“…As a periodontal pathogen, P. gingivalis may indirectly contribute to adverse pregnancy outcomes (APO) by facilitating the release of bacterial products or inflammatory mediators into the maternal circulation that reach the maternal-fetal interface [2]. P. gingivalis could also directly promote APO via invasion and injury to utero-placental tissues; this is supported by several studies that have detected P. gingivalis DNA/antigen in the placenta, amniotic fluid, umbilical cord, and neonatal nasogastric aspirates from complicated pregnancies [3][4][5][6][7][8][9][10][11]. However, the significance of P. gingivalis as a causative agent of APO is sometimes viewed with skepticism due to several confounding factors.…”
Section: Introductionmentioning
confidence: 63%
“…This was confirmed in vivo with a ligature model of periodontitis in rabbits that were inoculated with P. gingivalis strain A7436 or lipid phosphatase mutants that were 'locked' into producing a TLR4 agonist or antagonist [50]. In this study, all A7436 lipid A mutants altered the composition of the oral microbiota, but only TLR4 antagonist and wild-type A7436 enhanced the growth of Fusobacterium nucleatum, which is implicated in preterm delivery [53,54] and it is often found in association with P. gingivalis in placenta, amniotic fluid, and nasogastric aspirates from preterm infants [4,8]. Furthermore, the placenta is a blood-rich tissue and red blood cells contain hemin.…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…Nevertheless, this does not mean that oral bacteria are not implicated in the process leading to preterm birth as several studies have confirmed the dissemination of periodontal pathogens to extraoral sites in pregnancy [32,33]. Aagaard et al have also reported a very close similarity between placental and oral microbiomes [34].…”
Section: Page 6 Ofmentioning
confidence: 83%
“…Periodontal diseases may increase the systemic inflammatory challenge, due to hematogenous spread of bacteria and their products as a result of ulceration of epithelial cells in periodontal pockets [240,241]. P. gingivalis and T. denticola were found at a significantly higher level among the pregnant women with periodontitis [221].…”
Section: Periodontal Diseases and Gdmmentioning
confidence: 99%